Enhancing cycle stability and storage property of LiNi0.8Co0.15Al0.05O2 by using fast cooling method. (10th February 2017) - Li, Xiang; Ge, Wujie; Wang, Hao; Yan, Xinxiu; Deng, Bangwei; Chen, Tao; Qu, Meizhen
Abstract: The electrochemical performance and storage properties of Ni-rich cathode materials (LiNi0.8 Co0.15 Al0.05 O2 ) are improved via fast cooling methods (fast and ultrafast cooling). X-ray diffraction (XRD) results demonstrate that the interslab thickness of a fast-cooled sample is larger, and the degree of cation mixing is relatively lower, than in an untreated sample. X-ray photoelectron spectroscopy (XPS) confirms that the content of Ni 3+ on the surface of a fast-cooling treated sample is lower, while the average valence state of Ni obtained via titration is higher, than in the untreated sample, indicating the existence of a surface layer with less Ni 3+ for as-treated samples. Electrochemical characterizations confirm that as-treated samples display better cycling stability at 25 °C and 55 °C, as well as better rate capability, consistent with the XRD results. Fourier-transformed infrared spectrum (FTIR), XRD and electrochemical analysis confirm that the storage properties of fast-cooled samples are also enhanced. These results suggest that fast-cooled LiNi0.8 Co0.15 Al0.05 O2 with less Ni 3+ at the surface and larger interslab thickness in the bulk is a promising cathode material for high performance lithium ion batteries.